PENGARUH PEMBIAYAAN MURABAHAH, MUSYARAKAH DAN NON PERFORMING FINANCING TERHADAP PROFITABILITAS PERBANKAN SYARIAH (Studi pada Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2019)
This study aims to analyze the influence of Murabahah, Musyarakah and nonperforming financing on the level of profitability at Islamic Commercial Bank (Survey on Islamic Banking listed on BEI from 2014 to 2016). The research method used is a quantitative approach using survey method. The data are obtained through the publication result from the relevant Islamic Commercial Bank and accessed on www.bi.go.id. The analysis method used is multiple linear regression analysis. The results of the research indicate that: (1) Murabahah financing and Non Performing Financing Ratio has a significant effect on profitability projected through Return on Asset (ROA) at Islamic Commercial Banks in Indonesia, (2) Musyarakah financing has no significant effect on profitability projected through Return on Assets (ROA) in Islamic commercial banks in Indonesia.